OPTIMALISASI PEMBERDAYAAN WAKAF PRODUKTIF DI INDONESIA (IKHTIAR STRATEGIS DALAM MEMBANGUN KESEJAHTERAAN EKONOMI KEUMATAN) - Amarudin, Muchamat (LIPI, 2019)
Dealektika about waqf, cannot be released with the aspirations of the welfare of the people. However, realizing this is not an easy thing to do, because welfare does not only include one or two aspects, but also must look at the conditions, including implementing some fundamental principles in life and community and national life. So that waqf in Indonesia is able to develop well and can truly improve the social and economic welfare of the ummah, then it is time in Indonesia to formulate various matters relating to waqf, especially regarding assets that may be represented, the designation of waqf, nadzir waqf and how to manage endowments.